Kallikrein-related peptidases represent attractive therapeutic targets for ovarian cancer. (2nd September 2018) - Loessner, Daniela; Goettig, Peter; Preis, Sarah; Felber, Johanna; Bronger, Holger; Clements, Judith A.; Dorn, Julia; Magdolen, Viktor
ABSTRACT: Introduction : Aberrant levels of kallikrein-related peptidases (KLK1-15) have been linked to cancer cell proliferation, invasion and metastasis. In ovarian cancer, the KLK proteolytic network has a crucial role in the tissue and tumor microenvironment. Publically available ovarian cancer genome and expression data from multiple patient cohorts show an upregulation of most KLKs. Areas covered : Here, we review the expression levels of all 15 members of this family in normal and ovarian cancer tissues, categorizing them into highly and moderately or weakly expressed KLKs, and their association with patient prognosis and survival. We summarize their tumor-biological functions determined in cell-based assays and xenograft models, further highlighting their suitability as cancer biomarkers and attractive candidates for drug development. Finally, we discuss some different pharmaceutical approaches, including peptide-based and small molecule inhibitors, cyclic peptides, depsipeptides, engineered natural inhibitors, antibodies, RNA/DNA-based aptamers, prodrugs, miRNA and siRNA. Expert opinion : In light of the results from clinical and tumor-biological studies, together with the available pharmaceutical tools, we suggest KLK4, KLK5, KLK6 and possibly KLK7 as preferred targets for inhibition in ovarian cancer.